2016
DOI: 10.1371/journal.pone.0162167
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipolysis and Adipose Tissue Signaling during Acute Endotoxin-Induced Inflammation: A Human Randomized Crossover Trial

Abstract: BackgroundLipolysis is accelerated during the acute phase of inflammation, a process being regulated by pro-inflammatory cytokines (e.g. TNF-α), stress-hormones, and insulin. The intracellular mechanisms remain elusive and we therefore measured pro- and anti-lipolytic signaling pathways in adipocytes after in vivo endotoxin exposure.MethodsEight healthy, lean, male subjects were investigated using a randomized cross over trial with two interventions: i) bolus injection of saline (Placebo) and ii) bolus injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…GPCR40 is highly expressed in pancreatic beta cells and plays a crucial role in FFA‐induced insulin secretion . LPS treatment in humans has been shown to stimulate lipolysis, which is observed in the early stages of acute inflammation and sepsis . It is very much possible that the increase in insulin levels is due to the induction of lipolysis in the HFD supplemented animals, and with surplus of FFAs that can induce insulin release by the fatty acid receptors in the pancreases.…”
Section: Discussionmentioning
confidence: 99%
“…GPCR40 is highly expressed in pancreatic beta cells and plays a crucial role in FFA‐induced insulin secretion . LPS treatment in humans has been shown to stimulate lipolysis, which is observed in the early stages of acute inflammation and sepsis . It is very much possible that the increase in insulin levels is due to the induction of lipolysis in the HFD supplemented animals, and with surplus of FFAs that can induce insulin release by the fatty acid receptors in the pancreases.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms behind this upregulation of lipolysis have hardly been addressed. One study showed that LPS infusion in human subjects led to an increased phosphorylation of hormone sensitive lipase (HSL) at Ser 650 , a modification known to activate the enzyme (Rittig et al , ). HSL is one of the best described lipases (encoded by the LIPE gene) and could, together with the other important enzyme adipose triglyceride lipase (ATGL, PNPLA2 gene), be involved in the (patho)physiological lipolysis in white adipose tissue (WAT).…”
Section: Sepsis and Fatty Acid Metabolismmentioning
confidence: 99%
“…HSL is one of the best described lipases (encoded by the LIPE gene) and could, together with the other important enzyme adipose triglyceride lipase (ATGL, PNPLA2 gene), be involved in the (patho)physiological lipolysis in white adipose tissue (WAT). Also, cAMP‐dependent protein kinase A (PKA)‐dependent phosphorylation of perilipin 1 (PLIN1) is a decisive step in the activation of lipolysis (Choi et al , ) and was found to be elevated after LPS infusion (Rittig et al , ). This suggests that increased PKA activity might be one of the driving forces behind the increased lipolysis.…”
Section: Sepsis and Fatty Acid Metabolismmentioning
confidence: 99%
“…A diet rich in saturated fatty acids is considered to elicit a metabolic inflammation by promoting intestinal permeation to LPS. In contrast, injection of LPS causes a significant serum FFA increase in vivo . LPS has been shown to decrease the utilization of FFA by inhibiting triglyceride synthesis, suppressing the oxidation of FFA and stimulating lipolysis in adipose tissue, thereby increasing the circulating levels of FFA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, injection of LPS causes a significant serum FFA increase in vivo . LPS has been shown to decrease the utilization of FFA by inhibiting triglyceride synthesis, suppressing the oxidation of FFA and stimulating lipolysis in adipose tissue, thereby increasing the circulating levels of FFA. A low‐dose lipid infusion increases serum FFA levels, and monocytes exposed to lipid infusion in vivo enhance the in vitro secretion of pro‐inflammatory cytokines stimulated by LPS.…”
Section: Discussionmentioning
confidence: 99%